Quarter Life Crisis pada early adulthood: Bagaimana tingkat resiliensi pada dewasa awal? - Rahmah, Amelia Fitria Rahmah; Dwi Sarwindah Sukiatni; Rahma Kusumandari (INNER: Journal of Psychological Research, 2023)
Abstract The purpose of this study was to determine the level of resilience in young adults who experience a quarter-life crisis. This study uses a quantitative research approach. The population in this study were men and women aged 20-29 years, domiciled in Surabaya, and felt they were experiencing a quarter-life crisis such as worrying or worrying about the future, overthinking and being insecure about life, or being confused about life goals. The samples taken were 96 respondents with an accidental sampling technique. The results of data analysis using product moment correlation and there is a negative relationship between variable (X) and variable (Y) with a perfect correlation degree and a value of -0.823 with (p<0.000) are obtained. Future researchers can link quarter-life crises with other variables, so that research on quarter-life crises is more diverse. Keywords: Quarter Life Crisis, Resilience, Early Adulthood.